2003
DOI: 10.1002/app.12855
|View full text |Cite
|
Sign up to set email alerts
|

Tensile modulus modeling of carbon‐filled nylon 6,6 and polycarbonate‐based resins

Abstract: Electrically and thermally conductive resins can be produced by adding conductive fillers to insulating polymers. Mechanical properties, such as tensile modulus, are also important. This research focused on performing compounding runs followed by injection molding and tensile testing of carbon-filled nylon 6,6 and polycarbonatebased resins. The three carbon fillers investigated included an electrically conductive carbon black, synthetic graphite particles, and a milled pitch-based carbon fiber. For each polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…(10)–(13)] appear to give reasonable results for SG/PP, CB/PP, and CNT/PP composites. This is consistent with that seen in the earlier study of Konell et al52 for carbon black and synthetic graphite fillers in nylon 6,6 and in polycarbonate resins. However, Keith et al61 found that for composites containing synthetic graphite in Vectra, the Halpin‐Tsai models performed the best, with the Nielsen model underpredicting the tensile modulus.…”
Section: Tensile Modulus Modelingsupporting
confidence: 93%
See 2 more Smart Citations
“…(10)–(13)] appear to give reasonable results for SG/PP, CB/PP, and CNT/PP composites. This is consistent with that seen in the earlier study of Konell et al52 for carbon black and synthetic graphite fillers in nylon 6,6 and in polycarbonate resins. However, Keith et al61 found that for composites containing synthetic graphite in Vectra, the Halpin‐Tsai models performed the best, with the Nielsen model underpredicting the tensile modulus.…”
Section: Tensile Modulus Modelingsupporting
confidence: 93%
“…In Figure 6 it can be seen that higher concentrations of all carbon fillers in the polypropylene matrix caused an increase in the tensile modulus of the composite. This can be explained by the fact that the tensile modulus of the fillers is much higher than that of the neat polypropylene 49, 52–54. The adhesion between the filler and the matrix may also contribute to this effect, and will be described in a following subsection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the tensile modulus for the talc/CE composites along with the models discussed earlier. In the models described above, the following values were used .…”
Section: Resultsmentioning
confidence: 99%
“…The Halpin‐Tsai model has been used to model the tensile modulus of composites containing CNT and GNP 26, 29–32. The Nielsen and Halpin‐Tsai models have been used to model tensile modulus of CB/nylon 6,6, CB/polypropylene, and CNT/polypropylene composites 33–37. Both of these models account for constituent properties, concentrations of each constituent, as well as aspect ratio, orientation, and packing of the filler 29, 33–35…”
Section: Introductionmentioning
confidence: 99%